Educación literaria, literatura infantil y juvenil: una propuesta multicultural = Literary education, children and young adults’ literature: a multicultural proposal - Rechou, Blanca-Ana Roig (Educação)
It is adresses the consideration of literary education and its objectives; the importance of knowing each own country’s Children and Young Adults’ Histories, the canonized works from Universal Literature, repertoire and sectorial studies which educate mediators in order to create the convenient canons to promote reading. They are offered the commentaries on two Galician Children and Young Adults’ Literature works aimed towards multicultural education